2006
DOI: 10.1354/vp.43-6-896
|View full text |Cite
|
Sign up to set email alerts
|

The Immunohistochemical Characterization of Devil Facial Tumor Disease (DFTD) in the Tasmanian Devil (Sarcophilus harrisii)

Abstract: Immunohistochemical techniques were used to characterize the disfiguring and debilitating fatal neoplastic disease, devil facial tumor disease (DFTD), which has recently affected a significant proportion of the wild population of Tasmanian Devils (Sarcophilus harrisii). The diagnostic values of a number of immunohistochemical stains were employed to further characterize 50 representative cases. The neoplasms were negative for cytokeratin (0/48), epithelial membrane antigen (0/42), von Willebrand factor (vWF) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 30 publications
(40 reference statements)
1
70
0
Order By: Relevance
“…Although undifferentiated in appearance, DFTD has been characterized histologically as a tumor of neuroendocrine origin due to its expression of vimentin, S100, Melan A, CgA, NSE and synaptophysin, and the absence of expression of epithelial, neural, endothelial and hematopoietic markers (Table 1; Loh et al, 2006a, b). Only 32% of DFTD cases showed evidence of immune cell infiltration (Loh et al, 2006b).…”
Section: Dftdmentioning
confidence: 98%
“…Although undifferentiated in appearance, DFTD has been characterized histologically as a tumor of neuroendocrine origin due to its expression of vimentin, S100, Melan A, CgA, NSE and synaptophysin, and the absence of expression of epithelial, neural, endothelial and hematopoietic markers (Table 1; Loh et al, 2006a, b). Only 32% of DFTD cases showed evidence of immune cell infiltration (Loh et al, 2006b).…”
Section: Dftdmentioning
confidence: 98%
“…It is not yet clear why DFTD-affected devils fail to develop effective immunological rejection for the facial tumor allografts that establish through devil-to-devil transfer of viable tumor cells. In a histological survey of DFTD-affected tumors, Loh et al (2006b) reported a paucity of lymphocyte infiltration in association with the tumors and this may be explained by low MHC diversity in the devil populations where high prevalence of DFTD has been detected . The apparent inability of DFTD-affected devils to recognize these neoplasms and develop a tumor-specific immunological response, coupled with the absence of any free-ranging devil cases demonstrating tumor regression reinforces the need to continue research into the immunogenetic aspects of this serious disease.…”
Section: Lymphoid Tissues Of the Tasmanian Devilmentioning
confidence: 99%
“…Devils affected by DFTD develop lesions around the face and neck (Loh et al 2006b), which can metastasize. Mortality of affected devils occurs owing to organ failure, secondary infection or an inability to feed (Loh et al 2006a;Pyecroft et al 2007).…”
Section: Introductionmentioning
confidence: 99%